Morning hypertension for stroke and cardiovascular: clinical pearls for primary care - Rasyid, Al; Wiyarta, Elvan (Universa Medicina, 2021)
Hypertension is the world’s leading cause of mortality and morbidity. One of the phenomena that commonly occur in hypertensive as well as normotensive patients, is morning hypertension. Blood pressure (BP) follows a diurnal rhythm, reaching its highest level during the morning hours and dropping to the lowest level at midnight. Transient increases in BP in morning hypertension plus persistent stressors within 24 hours are thought to increase target organ damage and trigger cardiovascular events. Therefore, ambulatory BP monitoring or morning home BP monitoring is recommended as a strong predictor of cardiovascular events. There are two types of morning hypertension according to its underlying mechanisms; the first one is called nocturnal hypertensive morning hypertension, and the other one is morning-surge hypertension. Numerous studies have proved that this phenomenon often leads to several acute cardiovascular events, such as stroke, coronary artery disease, and peripheral artery disease. To prevent these complications, cost-effective management is needed, especially for identifying accurate diagnostic tools, as well as creating specific regimens. Therefore, to achieve appropriate management of hypertension, including morning hypertension, long-acting antihypertensive drugs should be used, at full doses and in the form of combination therapy. The clinical usefulness of antihypertensive drugs with specific mechanisms for morning BP or split or timed dosing of long-acting drugs in controlling morning BP remains under investigation. More studies are needed, especially looking for other clinical evidence of the benefits of lowering BP in the morning. Home BP monitoring is recommended as a good choice for BP measurements, especially in the primary care setting.